Politique sociale et religion aux Etats-Unis : du « conservatisme compatissant » à l’ouragan Katrina - Taoufik Djebali (Revue LISA)
Breaking with the traditional conservatism championed by Ronald Reagan, George W. Bush wanted his social policy to move away from monetary considerations to embrace a religious and spiritual method in healing social ills. The Office of Faith-Based and Community Initiatives, located in the White House, was inaugurated a few days after Bush was sworn in. However, the Office was immediately plagued by internal strife, lack of funding and absence of political commitment. Hurricane Katrina (2005) dealt a serious political blow to the Republican President. But paradoxically, it reinforced the ideological hegemony of faith-based organizations. Indeed, following the relief efforts, faith-based organizations, rather than government, were hailed as effective instruments in the fight against poverty, distress, and deviance. This article will argue that contrary to this perception, faith-based organizations have a limited effect on poverty and that the Bush administration exploited them for political purposes.